Effects of banking sector cleanup on lending conditions: Evidence from Ukraine - Yuliya Bazhenova (Graduate Institute of International and Development Studies, 2023)
This study investigates the causal effects of the banking sector cleanup on lending conditions. To overcome the banking crisis consequences of 2014-2016, the National Bank of Ukraine changed its regulation approach to strict intolerance towards financially weak and opaque banks and launched the development of the macroprudential regulation concept. As a result, a significant number of banks, accounting for approximately one-third of pre-crisis banking assets, were declared insolvent or withdrawn from the market for other reasons. We analyze bank-firm-loan level data merged with information from borrowers' financial statements. Examining a significant set of loan, bank, and borrower characteristics, we cannot conclude that lending conditions have definitely tightened since the cleanup of the banking sector. On the one hand, banks reduce large exposures in response to stricter regulatory requirements, primarily for lending to related parties, thereby decreasing the loan amount on average. On the other hand, loan interest rates decline due to monetary policy easing. As the risks for banks gradually decreased over time, interest spreads also narrowed, which was reflected in lower loan prices. At the same time, banks deteriorate lending conditions for loss-making firms: loan size significantly decreases compared to the whole sample of firms, and interest rates rise. Furthermore, bank requirements for financial performance of corporates become more stringent and generally do not ease to pre-policy levels over time. Finally, the results suggest that the crucial factors for corporate borrowers to receive a loan from a new bank after their bank closure are firm profitability at the time of a new match and loans quality in closed banks.
Keywords: C21; C41; G21; G28; 330; banking sector cleanup; bank liquidations; lending conditions